Kemiskinan dan Perempuan Pedesaan: Sebuah Perspektif Hukum dan HAM - Nikodemus Niko (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This research aimed to discuss how the interconnectedness of law and human rights against the poverty issues that happen to women in rural areas. The State taking fully responsible over the well-being of its people, thus the poverty that happens to women in rural areas is a tragedy in which the State failed to protect the rights of its people. The result of literature review indicates that the law is still not in favor of upholding women's rights as evidenced by poverty dominates women in rural areas. Extensive support and networks are needed from various groups of people who are concerned with upholding human rights especially for women to save policies that deliberately subordinate women.